Analisis Pemanfaatan Oksidator Ramah Lingkungan sebagai Alternatif Amonium Perklorat dalam Propelan Komposit untuk Mendukung Kemandirian Industri Pertahanan - , Nurul Ilmi; Timbul Siahaan; I Nengah Putra; Rizky Dwiandra Putra; Aris Haryanto (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Composite propellants are the primary fuel in rocket propulsion systems, consisting of a binder, fuel, and oxidizer. Ammonium perchlorate (AP) has long been used as an oxidizer in composite propellants due to its high performance and optimal combustion characteristics. However, the use of AP has negative environmental impacts due to hydrogen chloride (HCl) emissions, which contribute to air pollution and the potential for acid rain. Therefore, environmentally friendly alternative oxidizers are needed to support the defense industry. This study employs a qualitative method based on a literature review to analyze alternative oxidizers such as ammonium nitrate (AN), ammonium dinitramide (ADN), hydrazinium nitroformate (HNF), and hexaazaisowurtzitane (HNIW). The findings indicate that ADN is the most promising alternative to AP due to its good oxygen balance, high specific impulse (Isp), and more environmentally friendly combustion products. Meanwhile, HNF and HNIW exhibit high performance but are less stable and more sensitive to shocks. AN is a more economical and readily available oxidizer; however, it has limitations in terms of thermal stability and burn rate. These alternative oxidizers have the potential to replace AP in reducing environmental impact while supporting the self-sufficiency of the defense industry, considering aspects of safety, energy efficiency, and environmental impact. Further research is needed to enhance the stability of ADN and develop more efficient and sustainable production strategies for alternative oxidizers.